USEFULNESS OF TWO-DIMENSIONAL ECHO STRAIN IN EVALUATION OF CARDIAC FUNCTION IN ELITE ATHLETES. (June 2018) - Tosi, B.; Leone, B.; Toncelli, L.; Modesti, P.A.; Galanti, G.
Abstract : Objective: Cardiovascular adaptation to sport training is influenced by many factors, including the intensity and the kind of sport practiced. The "Morganroth hypothesis" asserted that a static exercise characterized by a pressure load and dynamic (isotonic) exercise which involves a volume load to the heart lead to different myocardial adaptation patterns. More recent studies revisited this hypothesis, showing that left ventricular (LV) remodelling observed in both resistance and endurance trained athletes, presented similar aspects. Although morphological modifications secondary to exercise have been largely studied, less is known on myocardial systolic function in LV remodeling patterns in different elite athletes. Two-dimensional strain analysis allows a complete study of the contractile function in different myocardial regions of interest in both ventricles. In this study we aim to underline possible differences in contractile myocardial function with strain analysis in two groups of elite athletes, trained with different loads and playing different sports (football and cyclism) Design and method: We enrolled 47 male athletes: 23 football players and 24 cyclists, belonging to same football or cyclism team (mean age in both groups 18 ± 3 years old). The athletes were evaluated with echocardiography at the beginning of the sports season. We assessed LV contractile function using speckle-tracking echocardiographic global longitudinal strain (GLS) and global circumferential strain (GCS). We also analysed right ventricular function by strain echocardiography Results: Cyclists showed a significantly augmented indexed LV mass and TAPSE. No significant differences were found in GLS data between the two groups (−23.4 ± 0.02 in football players and −24.1 ± 0.02 in cyclists), whereas a significantly higher GCS was found in cyclists compared to football players (−31.2 ± 0.04 and −27.2 ± 0.05 respectively, p < 0.005). The cyclist group showed a significant increase in right ventricular strain compared to football players (−26.3 ± 0.04 and −23.2 ± 0.04, respectively, p < 0.05) Conclusions: Our preliminary data suggest that a dynamic exercise, which involves a volume load, like cyclism, leads to a sensible increase in systolic function in elite athletes especially in right ventricle contractility.